2012
DOI: 10.1371/journal.pone.0037269
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Salmon Reovirus Infection Causes a CD8 T Cell Myocarditis in Atlantic Salmon (Salmo salar L.)

Abstract: Heart and skeletal inflammation (HSMI) of farmed Atlantic salmon (Salmo salar L.) is a disease characterized by a chronic myocarditis involving the epicardium and the compact and spongious part of the heart ventricle. Chronic myositis of the red skeletal muscle is also a typical finding of HSMI. Piscine reovirus (PRV) has been detected by real-time PCR from farmed and wild salmon with and without typical changes of HSMI and thus the causal relationship between presence of virus and the disease has not been ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
76
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 52 publications
(67 reference statements)
11
76
1
1
Order By: Relevance
“…Compared to the FF2 diet, relative levels were 25-fold higher in ST fish but, due to the high variability between individuals, this difference was not significant. The pathophysiological response to the infection characterised histologically by infiltration of lymphocytes and macrophages in heart tissue, reflected the pattern of viral load as had been shown earlier [3]. There was no infiltration of inflammatory or immune cells in heart tissue in any dietary group at 8-weeks post-challenge (Fig.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Compared to the FF2 diet, relative levels were 25-fold higher in ST fish but, due to the high variability between individuals, this difference was not significant. The pathophysiological response to the infection characterised histologically by infiltration of lymphocytes and macrophages in heart tissue, reflected the pattern of viral load as had been shown earlier [3]. There was no infiltration of inflammatory or immune cells in heart tissue in any dietary group at 8-weeks post-challenge (Fig.…”
Section: Resultssupporting
confidence: 68%
“…Heart and Skeletal Muscle Inflammation (HSMI) was first diagnosed in 1999 [1] and has been associated with a novel piscine reovirus [2] recently defined as Atlantic salmon reovirus (ASRV) [3]. It is currently one of the most prevalent inflammatory diseases in commercial Atlantic salmon farms in Norway, with over 600 sites affected since 2003.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, high levels of PRV transcripts were found in 28 of 29 diseased specimens, suggesting an association between PRV and HSMI. In Norway, this association has been strengthened by subsequent challenge studies and viral screenings from HSMI outbreaks which have confirmed that PRV is almost always detected during HSMI [48] and host antiviral responses are activated during this disease [811]. However, wild and farmed Atlantic salmon have also been shown to carry high loads of PRV in Norway without evidence of HSMI [1, 4, 12].…”
Section: Introductionmentioning
confidence: 99%
“…PRV is ubiquitous in Norwegian salmon farms [16,17], but there is a significant increase in the viral load and tissue distribution during outbreaks of HSMI [2,18]. The virus can be propagated in the GF-1 cell line [19], derived from the tissue of orange-spotted grouper, Epinephelus coioides [20], and cardiac and skeletal muscle pathology typical of HSMI can be reproduced in naïve Atlantic salmon by experimental inoculation with the supernatant from cell culture passaged PRV [19]. Most recently, it has been reported that serum enzymes creatine kinase and lactate dehydrogenase, associated with cardiac injury in humans [21], are significantly correlated with HSMI histopathology in Atlantic salmon [22].…”
Section: Introductionmentioning
confidence: 99%